Retrospective Study of Postoperative Pulmonary Complications in Patients with Cervical Spine Pathology - Dube, Surya Kumar; Pandia, Mihir Prakash; Chaturvedi, Arvind; Kumar, Shailender (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background Postoperative pulmonary complication (PPC) after cervical spine surgery is known to increase patient morbidity and mortality as well as the hospital and intensive care unit (ICU) stay. However, studies addressing this issue are scarce in the current literature. The aim of this study was to find out the incidence and various factors associated with PPC in patients undergoing cervical spine surgeries.Materials and Methods It is a retrospective study in a tertiary care hospital. Two hundred and seven patients who underwent different cervical spinal surgeries were included in this study. Various perioperative data including demography, history of smoking, associated systemic illness, type and site of lesion, preoperative respiratory status, and signs of involvement of lower cranial nerves were collected. The incidence and the risk factors for PPC were found out. Statistical analysis was done using chi-square/Fisher's exact test/Student's t-test, followed by univariate and multiple logistic regression analysis.Results The incidence of PPC in our study was 39.6%. Various pulmonary complications observed were difficulty in breathing requiring some intervention (19.3%), pneumonia (5.3%), tracheobronchitis (3.9%), arterial desaturation (3.4%), reintubation (3.4%), atelectasis (1.3%), pleural effusion (0.97%), pneumothorax (0.97%), and acute respiratory distress syndrome (ARDS) (0.97%). Preoperative respiratory abnormality, cervical laminectomy and instrumentation surgery and postoperative mechanical ventilation of > 24 hours duration were found to be independent risk factors for occurrence of PPC.Conclusions The patients with cervical spinal cord pathology are at increased risk for PPC. Preoperative respiratory abnormality, postoperative mechanical ventilation of > 24-hour duration, and cervical laminectomy and instrumentation surgery are independent risk factors for PPC.
Keywords: cervical spine; complications; pulmonary; risk factors